Myth vs. history in the natal narratives about pregnancy and birth - Лабащук, Оксана (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
In the article contemporary natal narrative is studied from the perspective of the influence of mythological and story types of texts on it. Natal narrative being similar to mythological text confirms some norms of world outlook and behavior. Natal narrative, like many texts of the story type, is about extraordinary events in a woman’s life or about an exceptional situation, which has happened to her acquaintances. The heroine of the natal narrative crosses a definite semantic border, reasserting the status of her exceptional nature.